Arctic-Alpine species in the bryoflora of the Altai-Sayan mountain region - Pisarenko Olga (EDP Sciences, 2021)
In the bryoflora the Altai-Sayan mountain region, 125 species have a predominantly Arctic-alpine distribution. A table of the locations geo-coordinates and habitat types in EUNI terms is compiled. The most common and rare species have been identified. The peculiarities of ecology and distribution of the species are discussed.